If it's not what You are looking for type in the equation solver your own equation and let us solve it.
18t-21=-21
We move all terms to the left:
18t-21-(-21)=0
We add all the numbers together, and all the variables
18t=0
t=0/18
t=0
| -4(1-4p)-4p=92p= | | -4c+18-9c=18-7 | | 6(-2x+9)=-6 | | (m+1)=2 | | (x+49)2=24 | | 3(x+2)=5x10 | | 3g+5=32 | | 16b-24+11=-13 | | 15x-5x=3x | | 4x2−2=34 | | 8s−1−8s=5+s | | 6x+3=8x-1=11x-7 | | -10=-6c+26 | | 2=4/6(x-3) | | 6x2=3x-5 | | 17=w/5+13/5 | | (8x-6)+(6x-8)+(84-3x)=180 | | -7+14x=2 | | 2/x-3=-5 | | (x−9)2=25 | | 9+7x=8x-6x | | 48÷n=6 | | x+x(1.5)+x(.5)=7.5 | | (3m-2)-m+2=4 | | 117-u=225 | | 0.5(8–6x)=4x+2 | | 3x^2+13=61 | | 5x-13/x-3=0 | | Y-23=y-6 | | 109=-v+258 | | 5/8b-4=-14 | | 6(y+3)=6(y+3)=30 |